Fuzzy-recurrent network based distributed frequency control of multi microgrid system - Kandasamy, Jeevitha; Ramachandran, Rajeswari; Veerasamy, Veerapandiyan; Irudayaraj, Andrew Xavier Raj (IEEE, 2023)
This paper proposes a distributed control strategy (DCS) for coordinating frequency control of multi microgrid (MMG) system. A leader-follower based consensus control law is derived for controlling each individual MG in the cluster. An adaptive fuzzy tuned recurrent neural network (FRNN) technique is proposed to design the optimal fractional order proportional-integral-derivative (FOPID) controller for distributed generation in the MG. A Lyapunov based objective function is developed to derive the dynamics, for weight updation of the RNN through gradient descent approach. The initial bias values of RNN are obtained via the Fuzzy approach for optimal operation of the FOPID controller. The proposed controller is tested for distributed frequency control of the MG system which coordinately controls the frequency of the MMG system. The performance of the controller is validated through various test cases and implemented in Hardware-in-the-loop using OPAL-RT simulation. The results show that the proposed control outperforms than other state-of-the-art.